2017
DOI: 10.3389/fpsyg.2017.01089
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Thematic Roles through Implicit Learning: Evidence from Light Verb Constructions

Abstract: The syntactic structure of a sentence is usually a strong predictor of its meaning: Each argument noun phrase (i.e., Subject and Object) should map onto exactly one thematic role (i.e., Agent and Patient, respectively). Some constructions, however, are exceptions to this pattern. This paper investigates how the syntactic structure of an utterance contributes to its construal, using ditransitive English light verb constructions, such as “Nils gave a hug to his brother,” as an example of such mismatches: Hugging… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 27 publications
4
9
0
Order By: Relevance
“…However, unlike idioms, light verbs have also been proposed to participate in argument sharing: In addition to being associated with the two event participants of typical agent‐patient verbs, light verbs may also inherit the dative event structure from the main verb itself (e.g., Jackendoff, ; Wittenberg et al., ). This type of account accords well with existing data showing that participants treat light verbs differently from compositional datives (Wittenberg et al., ), and typically as intermediate between compositional datives and canonical agent‐patient verbs (Wittenberg & Snedeker, ; Wittenberg et al., ). For example, Wittenberg and Snedeker (; see also Wittenberg et al., ) found that participants treated light verbs as having three rather than two event participants at least some of the time (23%), although the overwhelming majority of cases were treated as two‐participant events (75%) .…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…However, unlike idioms, light verbs have also been proposed to participate in argument sharing: In addition to being associated with the two event participants of typical agent‐patient verbs, light verbs may also inherit the dative event structure from the main verb itself (e.g., Jackendoff, ; Wittenberg et al., ). This type of account accords well with existing data showing that participants treat light verbs differently from compositional datives (Wittenberg et al., ), and typically as intermediate between compositional datives and canonical agent‐patient verbs (Wittenberg & Snedeker, ; Wittenberg et al., ). For example, Wittenberg and Snedeker (; see also Wittenberg et al., ) found that participants treated light verbs as having three rather than two event participants at least some of the time (23%), although the overwhelming majority of cases were treated as two‐participant events (75%) .…”
Section: Discussionsupporting
confidence: 89%
“…This type of account accords well with existing data showing that participants treat light verbs differently from compositional datives (Wittenberg et al., ), and typically as intermediate between compositional datives and canonical agent‐patient verbs (Wittenberg & Snedeker, ; Wittenberg et al., ). For example, Wittenberg and Snedeker (; see also Wittenberg et al., ) found that participants treated light verbs as having three rather than two event participants at least some of the time (23%), although the overwhelming majority of cases were treated as two‐participant events (75%) . However, in our Experiment 1, we found no difference between idioms and light verbs in their effectiveness as primes for compositional dative targets; if anything, idioms were slightly better primes than light verbs.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The eye-movement data were analyzed using a nonparametric permutation test involving the comparison between a linear mixed effects model fitted to the data and reference linear mixed effects models fitted to permuted datasets, which allowed us to test whether our predictors were associated with an increase in looks to the NP 1 character at any time during our auditory region of interest, without the need for specific hypotheses about when looking patterns would diverge (Maris and Oostenveld, 2007;Wittenberg et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Crucially, because they are not fully compositional, idioms and light verbs do not have the same semantic representations that compositional dative structures do Wittenberg, Khan, & Snedeker, 2017). Both variants of compositional datives, for instance, involve three event participants, differentiated from each other either by their event structures or thematic mappings ( Fig.…”
Section: The Semantic and Syntactic Representations Of Idioms Light mentioning
confidence: 99%